Analisis Kontribusi dan Strategi Pengelolaan Badan Usaha Milik Desa (BUMDes) Lambangsari dalam Meningkatkan Pendapatan Asli Desa - Dwi Ratna Sari; Petrolis Nusa Perdana; Rochma Sudiati (LPPM Universitas Negeri Jakarta, 2026)
Village-Owned Enterprise (BUMDes) was established by the government with a focus on managing village potential to increase Village Original Revenue (PADes). However, in practice, various problems have caused the performance of BUMDes to remain suboptimal. This study aims to analyze the contribution of BUMDes to PADes and to formulate management strategies for BUMDes. The research employed a descriptive quantitative method using secondary data from the Village Budget Realization Reports (APBDes) Lambangsari for the period 2022–2025, as well as primary data obtained through interviews. The results of this study indicate that the contribution provided by BUMDes Lambangsari to PADes remains fluctuating and tends to be less than optimal.